2021
DOI: 10.37310/ref.v90i1.2715
|View full text |Cite
|
Sign up to set email alerts
|

Há efeito da idade relativa em nadadores do campeonato mundial de esportes aquáticos de Budapeste 2017?

Abstract: Introdução: O efeito da idade relativa (EIR) pode ser entendido como a diferença na idade cronológica de indivíduos nascidos no mesmo ano de seleção, bem como pelas vantagens maturacionais em relação a seus pares nascidos no mesmo ano, o que parece favorecer o desempenho para determinadas categorias esportivas. Objetivo: Verificar a presença do EIR em nadadores participantes do Campeonato Mundial de Esportes Aquáticos Budapeste 2017.Métodos: Estudo seccional retrospectivo, que utilizou dados secundários, do qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Thus, Born et al (2022) reported that RAEs were more likely to occur in athletes that competed in longer race distances when analyzing male and female non-Paralympic swimmers, regardless of swimming strokes. On the other hand, Lemos et al (2021) found RAE in sprint events, and not in middle-distance and long-distance events in non-Paralympic swimmers. Clearly, many performance factors exert influence on the existence of RAE in swimmers, and the specificities of the Para-swimming sport modality seem to contribute to an even more complex context, indicating the need for more information on the relationship between RAE and Paralympic sports.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, Born et al (2022) reported that RAEs were more likely to occur in athletes that competed in longer race distances when analyzing male and female non-Paralympic swimmers, regardless of swimming strokes. On the other hand, Lemos et al (2021) found RAE in sprint events, and not in middle-distance and long-distance events in non-Paralympic swimmers. Clearly, many performance factors exert influence on the existence of RAE in swimmers, and the specificities of the Para-swimming sport modality seem to contribute to an even more complex context, indicating the need for more information on the relationship between RAE and Paralympic sports.…”
Section: Discussionmentioning
confidence: 55%